Hubungan Aktivitas dan Respon Emosi Estetik pada Konten Foto Instagramable Interior Coffee Shop Terhadap Visit Intention - Munggarsari, Annisa Amalia; Ahmad, Hafiz Aziz (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Today, coffee shops are not only a place to drink coffee, but also a symbol of urban lifestyle. The transformation of the function of coffee shop space from a place to discuss to a place to socialize and work and even take pictures has a significant impact on visitor preferences. These preferences are currently influenced by social media content, especially Instagram as a photographic platform with the largest number of users. Instagrammable photo content not only triggers aesthetic emotional responses, but also influences visit intention behavior. This study aims to explore the relationship between user activity, aesthetic emotional response, and its impact on visit intention in the context of Instagrammable photo content of coffee shop interiors. The research method used mixed methods, qualitative and quantitative. The results showed that user activity motivations, such as gathering, eating and drinking, working, taking pictures and aesthetic emotional responses were positively correlated with visit intention. There is a tendency for audiences to choose content with warm color ambience for activities such as working or eating and drinking coffee, while gathering and photo activities are more likely to choose content with vibrant ambience.